Unlocking Indigenous Plants for restoring degraded silvopastoral systems - Louhaichi, Mounir; Kailene, Jamel; Hamrouni, Lamia; Belgacem, Azaiez Ouled; Hassan, Sawsan (CGIAR System Organization, 2024)
Unlocking indigenous plants as innovative solutions for restoring agro-ecological zones under changing climate in the dry areas.